Reconciling mass functions with the star-forming main sequence via mergers. Issue 1 (28th February 2017) - Steinhardt, Charles L.; Yurk, Dominic; Capak, Peter
Abstract: We combine star formation along the 'main sequence', quiescence and clustering and merging to produce an empirical model for the evolution of individual galaxies. Main-sequence star formation alone would significantly steepen the stellar mass function towards low redshift, in sharp conflict with observation. However, a combination of star formation and merging produces a consistent result for correct choice of the merger rate function. As a result, we are motivated to propose a model in which hierarchical merging is disconnected from environmentally independent star formation. This model can be tested via correlation functions and would produce new constraints on clustering and merging.